Karakterisasi Pola Mineralisasi N Pupuk Organik Pada Tanah Sawah Organik - Winarni, Marti; Yudono, Prapto; Indradewa, Didik; Hendro Sunarminto, Bambang (JURNAL AGRI-TEK, 2015)
Organic rice cultivation rely only source of nutrients of organic fertilizers and other natural inputs. One way to meet the needs of nitrogen in organic rice cultivation is to utilize the organic fertilizers. The purpose of this study was to examine the influence of the type of organic fertilizers on N-available content in the soil, the characterization of the pattern of mineralization of N-available from types of organic fertilizer, and determine the three types of organic fertilizer which has a pattern of fast nitrogen mineralization, medium and slow. This research was conducted through experimental methods in greenhouse Faculty of Agriculture of Gadjah Mada University from November 2012 until May 2013. Experiments using randomized completely design (RCD), consisting of 1 factor and 3 replications. These factors is incubation organic fertilizer in soil organic lowland, consisting of 10 types: Callyandra callothyrsus, Leucaena leucocephala, Sesbania grandiflora, Albizia falcata, Cassia siamea, Gliricidia sepium, Samania saman, Herocarpus indica, manure, and control (without organic fertilizer). The results showed that the use of organic fertilizers can improve the content of N-available in the soil as compared to manure and without organic fertilizer. In general, the pattern of nitrogen mineralization of organic fertilizers on soil organic lowland started 3 weeks after incubation and increased up to 9 weeks after incubation, and then decreased 12 weeks after incubation period. Sesbania grandiflora, Gliricidia sepium and Leucaena leucocephala, respectively, have the character pattern nitrogen mineralization fast, medium and slow.Keywords: organic fertilizers, N mineralization, soil organic lowland